An Unusual Complication of Colonic Perforation Following Percutaneous Nephrostomy in a Grade IV Blunt Renal Injury Patient - Joan Gan Cheau Yan; Tan Jih Huei; Henry Tan Chor Lip; Yuzaidi Mohamad; Rizal Imran Alwi (Journal of Trauma and Injury)
Percutaneous nephrostomy is relatively safe for temporary urinary diversion. However, colonic perforation due to percutaneous nephrostomy can happen with an incidence of 0.2% as reported in the English literatures. To our knowledge, this is the first case being reported as a complication following treatment for traumatic renal injury. This paper is to share our treatment approach which differs from the usual approach according to existing literatures. We report on a young man who sustained grade IV renal injury due to blunt trauma and was managed conservatively. The treatment of traumatic renal injury via urinary diversion was complicated with an iatrogenic colonic perforation. The management and subsequent treatment of this patient is discussed in this case report.